Antibacterial properties of purified sago frond sugar against food-borne associated disease bacteria - Muhammad Norhelmi Ahmad; Nurazureen Matnin; Dayang Salwani Awang Adeni; Nurashikin Suhaili; Kopli Bujang (Penerbit Universiti Kebangsaan Malaysia, 2023)
Sago palm is recognised as key to sustainable food security due to its advantages resilient against extreme conditions such as wildfire and flood associated with adaptability to climate change. Sago palm is also known to remain solid after being attacked by pests and infected by the disease. Unfortunately, for the last ten years, the Sago palm industry experiences a significant decrease in plantation area and productivity. The long maturation period is identified to be the major factor that is responsible towards the respected issue. Thus, alternative commodities from the growing sago palm must be explored to offer a better perspective on the sago industry. Sago frond (SF) was utilised into Sago Frond Sugar (SFS) via enzymatic hydrolysis using cellulase enzyme containing cellobiose and glucose as main sugar at 9-10 g/L and 5-6 g/L concentration respectively. SFS was purified (PSFS) using Powdered Activated Charcoal (PAC) to remove the impurities. Antibacterial analysis shows that PSFS able to inhibit the growth of Staphylococcus aureus, Escherichia coli and Salmonella typhi at 23.5 mm, 22.5mm and 13.25 mm clearing zone respectively. However, the growth of Listeria monocytogenes seems unaffected by the presence of PSFS. Promoting the versatility of sago frond as raw material to synthesise high-value products such as SFS will extend the potential of the sago palm to be recognised as an important crop to ensure global food security and safety.